The Efficacy of Porcine Dermal Collagen to Treat Complex Anal Fistulae. Results of a Multicenter Cohort - Placer, Carlos; Castillo, Julio; Loizate, Alberto; Baixauli, Jorge; Echeveste, Ainhoa; Cristobal, Lidia; Gonzalez, Eneko; Suarez, Natalia; Navascues, Jose Maria Enriquez (Journal of Coloproctology, 2023)
Introduction The management of complex anal fistulae remains a topical surgical problem. The choice and success of surgical management are based on the balance between healing and continence. Although porcine dermal collagen (Permacol Collagen Paste [PCP]- Covidien plc, Gosport, Hampshire, UK) represents a new generation of non-solid biomaterials, its results in anal fistulae are mixed.Methods A multicenter observational retrospective analysis of consecutive patients with cryptoglandular anal fistula treated in four colorectal surgery units was performed between 2015 and 2020. Clinical cure of the fistula was the main outcome measure. Adverse events and alterations in anal continence were secondary outcomes.Results The study included 119 patients (87 males, 71.1%), with a mean age of 53 years (IR 44–65). Most patients had complex (80.6%) and recurrent (91.6%) fistulae. With the first PCP treatment, the overall cure rate was 41.2% (49 patients) and 45.4% with the second treatment (5 out of 17 patients). The mean follow-up period was 17 months (IR 5–25). Healing was not affected by the location and type of fistula, the existence or not of a cavity, the number of tracts, or the administration of prophylactic antibiotics. After the PCP treatment, no patient in the series had worsening of continence. Morbidity affected 22.7% of the patients (27), with postoperative abscesses being the most frequent adverse event. There were no statistical differences between the four hospitals studied.Conclusions Permacol collagen paste is a safe and easily reproducible therapy for complicated anal fistulae that has moderate efficacy. The overall success rate is slightly over 40%, with no detriment to fecal continence.
Keywords: Permacol paste; anal fistula; complex anal fistula